Reconciling democracy and sustainability: three political challenges and the role of democratic innovations - Marquardt, Jens; Pfeiffer, Frederik; Blum, Mareike; Daw, Tim M.; Dugasseh, Frank Akowuge; Heitzig, Jobst; Hysing, Erik; Jensen; Ingrid Helene Brandt; Kulha, Katariina; Langkjaer, Frederik; Lindvall, Daniel; et al. (TAYLOR & FRANCIS LTD, 2025)
Governing sustainability challenges such as climate change or biodiversity loss presents a profound democratic dilemma. Although democratic practices and procedures are widely regarded as essential for collectively addressing complex sustainability issues, liberal democracies have been criticized by some scholars for their inability to effectively tackle global environmental threats like climate change. We reconcile these positions by outlining how the emerging field of democratic innovations can help to address the critical challenges that democracies face when governing sustainability transformations. We focus on three issues liberal democracies are confronted with: reformist incrementalism, (de)politicization, and imaginary boundaries. We then exemplify how democratic innovations such as deliberative mini-publics, participatory budgeting, and material participation can help address these challenges. Our review suggests that democratic innovations hold the potential to address political concerns, find compromises between extreme positions, reconnect people's everyday lives with the grand sustainability challenges they face, and allow for alternative visions of a desirable future society. However, we also address cautionary tales, discuss the limitations of democratic innovations, and outline avenues for future research, which we believe can help further elaborate and develop participatory approaches to critical sustainability challenges.